2019
DOI: 10.1111/adj.12695
|View full text |Cite
|
Sign up to set email alerts
|

A significant incidental finding on cone beam computed tomography: multiple myeloma

Abstract: Cone beam computed tomography is widely used in dentistry. Incidental findings are common, with many requiring intervention or monitoring. We present a rare case of previously undiagnosed, asymptomatic multiple myeloma first identified incidentally on cone beam computed tomography and panoramic radiography. This case highlights the diverse range of lesions that may appear on cone beam computed tomography and the importance of radiologic interpretation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The authors showed that no incidental discoveries of malignancies were observed in their study, indicating that they are relatively unusual findings [ 32 ]. In addition, reports of undiagnosed myeloma discovered incidentally on dental imaging are uncommon [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The authors showed that no incidental discoveries of malignancies were observed in their study, indicating that they are relatively unusual findings [ 32 ]. In addition, reports of undiagnosed myeloma discovered incidentally on dental imaging are uncommon [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…A dentist cannot elect to read and interpret only part of a bitewing, lateral cephalogram, or OPG 84 . Whilst the possibility of missing major problems is low, serious pathosis can be identified incidentally on dental CBCTs 85,86 . Incidental findings are common with dental CBCTs 87 (Fig.…”
Section: Radiographymentioning
confidence: 99%
“…84 Whilst the possibility of missing major problems is low, serious pathosis can be identified incidentally on dental CBCTs. 85,86 Incidental findings are common with dental CBCTs 87 (Fig. 3).…”
Section: Radiographymentioning
confidence: 99%